Non-pharmacological therapies in the treatment of chemotherapy-induced alopecia – a literature review - Ochońska, Izabela; Jaglarz, Karolina; Kuca, Maciej; Cholewa, Marcin; Jasiewicz, Maria (Journal of Education, Health and Sport, 2025)
Introduction and Objective. Every year, 20 million people are diagnosed with cancer, most of whom undergo chemotherapy at some stage of treatment. Chemotherapy is associated with various side effects, with hair loss being one of the most visible and socially stigmatizing. This study aimed to evaluate and summarize existing strategies for preventing chemotherapy-induced hair loss. Review methods. Data for this paper were gathered using electronic databases like PubMed and Google Scholar, with a focus on papers from the last five years, particularly clinical trials, double-blind randomized studies, meta-analyses, and reviews. State of Knowledge. Around 65% of chemotherapy patients experience hair loss. Currently, the FDA has approved one method for preventing chemotherapy-induced alopecia (CIA): scalp cooling. This technique induces localized vasoconstriction, reducing the penetration of chemotherapy drugs into hair follicles. Scalp cooling is generally well-tolerated. Other potential methods include scalp injections of autologous platelet-rich plasma, which contains growth factors and anti-inflammatory cytokines, and microneedling, an invasive procedure with uncertain effectiveness, especially as a standalone treatment, that aims to stimulate angiogenesis. Conclusions. Effective, reliable methods for preventing chemotherapy-induced alopecia (CIA) are still lacking. A holistic approach to oncology care is needed to address the diverse needs of patients. Discovering new preventive methods would greatly improve patients’ ability to cope with cancer treatment. However, most current approaches show only moderate efficacy or are still in clinical trials.